Mass deworming for improving health and cognition of children in endemic helminth areas: A systematic review and individual participant data network meta‐analysis. Issue 4 (20th November 2019) - Welch, Vivian A.; Ghogomu, Elizabeth; Hossain, Alomgir; Riddle, Alison; Gaffey, Michelle; Arora, Paul; Dewidar, Omar; Salam, Rehana; Cousens, Simon; Black, Robert; Hollingsworth, T. Déirdre; Horton, Sue; et al.
Abstract: Background: Soil transmitted (or intestinal) helminths and schistosomes affect millions of children worldwide. Objectives: To use individual participant data network meta‐analysis (NMA) to explore the effects of different types and frequency of deworming drugs on anaemia, cognition and growth across potential effect modifiers. Search Methods: We developed a search strategy with an information scientist to search MEDLINE, CINAHL, LILACS, Embase, the Cochrane Library, Econlit, Internet Documents in Economics Access Service (IDEAS), Public Affairs Information Service (PAIS), Social Services Abstracts, Global Health CABI and CAB Abstracts up to March 27, 2018. We also searched grey literature, websites, contacted authors and screened references of relevant systematic reviews. Selection Criteria: We included randomised and quasirandomised deworming trials in children for deworming compared to placebo or other interventions with data on baseline infection. Data Collection and Analysis: We conducted NMA with individual participant data (IPD), using a frequentist approach for random‐effects NMA. The covariates were: age, sex, weight, height, haemoglobin and infection intensity. The effect estimate chosen was the mean difference for the continuous outcome of interest. Results: We received data from 19 randomized controlled trials with 31, 945 participants. Overall risk of bias was low. There were no statistically significant subgroup effects across any of the potential effect modifiers. However, analyses showed that there may be greater effects on weight for moderate to heavily infected children (very low certainty evidence). Authors' Conclusions: This analysis reinforces the case against mass deworming at a population‐level, finding little effect on nutritional status or cognition. However, children with heavier intensity infections may benefit more. We urge the global community to adopt calls to make data available in open repositories to facilitate IPD analyses such as this, which aim to assess effects for the most vulnerable individuals.